The Employment Consequences of Seniority Wages - Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper combines two strains of the literature on the employment effects of deferred compensation. The first strain separates seniority and job matching wage effects on the basis of individual data, but cannot look at employment consequences. The second strain explains the employment structure on the basis of establishment data, but cannot properly calculate seniority wages. This paper uses linked employeremployee data, aggregates individual seniority wages to the establishment level, and correlates them with the establishment employment structure. According to the deferred compensation hypothesis this paper finds that establishments with stronger seniority wages have a higher tenure but hire less older employees.
Keywords: J31; J14; J21; 330; Seniority Wages; Employment Structure; Linked Employer-Employee Data; Senioritätsentlohnung; Betriebszugehörigkeit; Lohn; Ältere Arbeitskräfte; Arbeitsnachfrage; Arbeitsmobilität; Arbeitslosigkeit; Deutschland